2015
DOI: 10.1109/jlt.2015.2430373
|View full text |Cite
|
Sign up to set email alerts
|

Laser Rate Equation-Based Filtering for Carrier Recovery in Characterization and Communication

Abstract: Abstract-We formulate a semiconductor laser rate equationbased approach to carrier recovery in a Bayesian filtering framework. Filter stability and the effect of model inaccuracies (unknown or un-useable rate equation coefficients) are discussed. Two potential application areas are explored: laser characterization and carrier recovery in coherent communication. Two rate equation based Bayesian filters, the particle filter and extended Kalman filter, are used in conjunction with a coherent receiver to measure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The variable Ω k is a normalized frequency that models a drift of the differential laser frequency as a random walk with variance σ 2 Ω [25]. Additionally, ϕ k is affected by a random walk with variance σ 2 ϕ .…”
Section: Particle Smoothermentioning
confidence: 99%
“…The variable Ω k is a normalized frequency that models a drift of the differential laser frequency as a random walk with variance σ 2 Ω [25]. Additionally, ϕ k is affected by a random walk with variance σ 2 ϕ .…”
Section: Particle Smoothermentioning
confidence: 99%
“…Nonlinear phase noise compensation: [18][19][20][21][22] Modulation format identification: [10][11] Optical signal monitoring: [13][14][15] Nonlinearity compensation: [23] Amplitude, phase and nonlinear phase noise: [3][4][5][6][7][8] Optical performance monitoring: [12,[16][17], Nonlinear phase noise compensation: [19,22] Cognitive receiver design:…”
Section: Clustering K-meansmentioning
confidence: 99%
“…However, the majority of the proposed methods do not offer an optimum and joint estimation of photon number and optical phase in the presence of the measurement noise. We have recently demonstrated that the techniques from machine learning can be used to perform optimum optical phase detection and thereby enable accurate laser FN characterization 4,5 . The presented framework used Bayesian state-space based inference and employed small signal laser rate equation.…”
Section: Introductionmentioning
confidence: 99%